2021
DOI: 10.1111/jam.15073
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of single cultures and a consortium of white rot fungi for polychlorinated biphenyls treatment

Abstract: Aims To evaluate the mycoremediation of polychlorinated biphenyls (PCBs) by either single cultures or binary consortia of Pleurotus pulmonarius LBM 105 and Trametes sanguinea LBM 023. Methods and Results PCBs tolerance, removal capacity, toxicity reduction and ligninolytic enzyme expression were assessed when growing single culture and binary consortium of fungus in 217 mg l−1 of a technical mixture of Aroclor 1242, 1254 and 1260 in transformer oil. A decrease in tolerance and variation in ligninolytic enzyme … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(1 citation statement)
references
References 68 publications
0
1
0
Order By: Relevance
“…The laccase enzyme plays a key role in the degradation of pollutants in the environment due to the activity of free radicals during the oxidation of aromatic compounds, phenolic compounds and amines, and this enzyme is used in biotechnology applications as a biocatalyst and basidiomycetes are the best in its secretion 33 . In recent years, some studies have shown that some anamorphic fungi could secrete this enzyme, which may be due to the mutations resulting from the nature of the environment in which the fungi live 34 .…”
Section: Nomentioning
confidence: 99%
“…The laccase enzyme plays a key role in the degradation of pollutants in the environment due to the activity of free radicals during the oxidation of aromatic compounds, phenolic compounds and amines, and this enzyme is used in biotechnology applications as a biocatalyst and basidiomycetes are the best in its secretion 33 . In recent years, some studies have shown that some anamorphic fungi could secrete this enzyme, which may be due to the mutations resulting from the nature of the environment in which the fungi live 34 .…”
Section: Nomentioning
confidence: 99%